PENGARUH KOMITMEN ORGANISASI, KARAKTERISTIK INDIVIDU DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN DI PUSAT PENELITIAN KELAPA SAWIT (PPKS) MEDAN - Nur Augus Fahmi (Jurnal Prodi Fakultas Ekonomi-UISU, 2019)
The formulation of the problem of this research is how the organizational commitment influence on employee performance, how to influence individual characteristics on employee performance, how emotional intelligence affects employee performance and how Influence of organizational commitment, individual characteristics and simultaneous emotional intelligence to employees ' performance at the Medan Oil Palm Research Center (PPKS).The population in this study was all the employees of Medan's Palm Research Center (PPKS) amounting to 37 people who were also samples. Data collection techniques using interviews and polls (questionnaires). Data analysis methods using SPSS version 22. The results showed that there was a positive and significant influence between the organizational commitment to employee performance at the Medan Oil Palm Research Centre (PPKS), there was a positive and significant influence between individual characteristics of performance Employees at the Medan Oil Palm Research Center (PPKS), there are further positive and significant influences between the emotional intelligence of employees ' performance at the Medan Oil Palm Research Centre (PPKS), and there is a positive and significant influence Between organizational commitments, individual characteristics and emotional intelligence to employees ' performance at the Medan Oil Palm Research Center (PPKS).Keywords : Organizational Commitments, Individual Characteristics, Emotional Intelligence, Employee Performance